(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
The paper considers the role of atlas cartographic justification of tourism and recreation organization in the context of rational use of natural resources of regional territorial units. Cartographic justification of the use of these resources is currently relevant especially in mountainous and densely populated geosystems, where, along with natural factors, anthropogenic factors are most actively manifested in various parts of these territorial units. Based on the atlas cartographic database, it will be possible to document the availability of conditions for potential prerequisites for recreational and tourist resources, both in large and smaller territorial units. When forming the structure of the atlas content, it is necessary to classify its data according to their importance in this region, according to the possibilities and nature of their use. It is also necessary to take into account the possible environmental problems of the regions and draw up specific maps and schemes of environmental action projects.